PENGARUH HUBUNGAN INDUSTRIAL DAN PERAN SERIKAT PEKERJA TERHADAP KESEJAHTERAAN KARYAWAN KONTRAK PADA PT. SARI LEMBAH SUBUR KECAMATAN PANGKALAN LESUNG KABUPATEN - Desy Rahmawati Savitri; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the influence of industrial relations and the role of trade unions on the welfare of contract employees at PT.Sari Lembah Subur, Pangkalan Lesung District, Pelalawan Regency, Riau.In this research, the methods used are descriptive and quantitative. Data obtained from interview data and distributing questionnaires via google from then tested with statistics through the SPSS program. The sample used was 71 employees of PT Sari Lembah Subur contract, Pangkalan Lesung District, Pelalawan Regency, Riau.The method of analysis used in this research is simple and multiple regression analysis, and through validity and reliability tests. In this study the results obtained are that Industrial Relations have a positive and significant effect on employee welfare, the role of trade unions has a positive and significant effect on the welfare of contract employees, and Industrial Relations and the Role of Trade Unions have a positive and significant effect on the Welfare of Contract Employees at PT. Sari Lembah Subur, Pangkalan Lesung District, Pelalawan Regency, Riau. Keywords: Industrial Relations, Worker Unions, Employee Welf